The Analysis of the Land Cover Changes to Surface Flows of Bulok Watershed, Lampung Province - Aprianto, Dian; Ristiara, Liana (FAKULTAS PERTANIAN UNIVERSITAS RATU SAMBAN, 2024)
The Way Bulok Watershed (DAS) is a tributary of the Way Sekampung Watershed which is administratively located in Pringsewu Regency, Lampung Province. The use of land cover due to increasing human numbers and activities has a significant impact on surface flow (runoff) of the Way Bulok Sub-watershed. This research aims to analyze changes in land cover and to determine the effect of changes in land cover on surface flow in the Way Bulok Sub-watershed area. The results of research conducted show that total rainfall has increased, in 2011 rainfall was 1342 mm/year and in 2017 it increased to 1570 mm/year. This is in line with the increase in river discharge, where the annual average river discharge in 2011 was 21.69 m3/s, increasing to 35.40 m3/s in 2017. Likewise, the surface flow coefficient value has increased from 0 .19 to .27 . The land cover in the Way Bulok Sub-watershed area is still dominated by agricultural areas which have an area of more than 50% each year, compared to the forest area which is only 2,123% of the total area of the Way Bulok Sub-watershed in 2017.